The Hellenistic age a short history - Green, Peter 1924-2024 (Modern Library, 2007)
Covering three centuries of history, from the age of Alexander the Great to the rise of Rome, a study of the Hellenistic period traces the influence of Greek culture on the ancient world.
Keywords: Geschichte; Hellenism; Hellenismus; Griechenland; Greece -- History -- 146 B.C.-323 A.D; Greece -- History -- To 146 B.C; Mediterranean Region -- History -- To 476